Dimensional Interval and Critical Sizes of Non-Legand Nano- and Microparticles. Issue 1 (October 2015) - Kharkhardin, A N; Strokova, V V; Kozhukhova, N I; Nelubova, V V
Abstract: The derivation of the equation for the calculation of the critical size of clusters and nanoparticles in the range of appearing of their unusual properties in comparison with the massive body as well as the equation for the calculation of the growth of spherical crystallites and aggregations is presented in the article.